2000
DOI: 10.1159/000020979
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Lymphocyte Culture of Human Fetal Liver Cells

Abstract: Objective: In order to study the immunological function of the human fetus in the first and second trimesters, mixed lymphocyte culture (MLC) of fetal liver and thymic cells was performed. MLC is a functional test to determine human lymphocyte antigen-D incompatibilities. Methods: Human fetal liver and thymic tissue was obtained from abortions in gestational weeks 7–17.5. Forty-seven fetuses were studied with one-way MLC. The cells were stimulated by adding irradiated fetal liver cells, adult bone marrow and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…We have found that FLCs can respond in MLC to a varying degree from the eighth gestational week. 24 However, since fMSCs suppress the proliferation induced by mitogens, it appears that they, at least possess some of the immunomodulatory properties found in aMSC. To conclude, fMSCs were successfully grown in culture.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that FLCs can respond in MLC to a varying degree from the eighth gestational week. 24 However, since fMSCs suppress the proliferation induced by mitogens, it appears that they, at least possess some of the immunomodulatory properties found in aMSC. To conclude, fMSCs were successfully grown in culture.…”
Section: Discussionmentioning
confidence: 99%
“…In the human fetus, intrauterine death also occurred from "overwhelming engraftment" [31] when the T-cell dose exceeded 10 8 /kg. While the fetus has been assumed to be "preimmune" [32,33], it is probably more correct to term the fetus "early immune," as immunocompetent cells are present very early in the fetus, suggesting that it is not truly devoid of immune function [34][35][36][37][38][39][40][41]. If one assumes that the fetus has some immune function, it is not surprising that a relatively large number of donor T cells are needed to ensure successful engraftment, presumably through a donor-versus-host effect.…”
Section: Discussionmentioning
confidence: 99%
“…2,8 Moreover, T cells showing TCR rearrangement have been observed in human FL in the 13th week of gestation, 26 and FL NK cells and fetal T cells have been demonstrated alloreactive in vitro. [27][28][29] These lines of evidence could indicate the engraftment failure of FL hematopoietic cells transplanted in utero in allogeneic recipients. 30,31 Recent studies suggest that an immunoreaction takes place when the fetus is exposed to allogeneic cells.…”
Section: Discussionmentioning
confidence: 99%